Azulene‐Based Macrocyclic Receptors for Recognition and Sensing of Phosphate Anions. Issue 49 (25th October 2016) - Lichosyt, Dawid; Dydio, Paweł; Jurczak, Janusz
Abstract: Herein we report the synthesis and detailed studies of the anion‐binding properties of two 20‐membered macrocyclic tetramide receptors: one symmetrical, containing two identical azulene‐based bisamide units, the other a hybrid, containing a dipicolinic bisamide unit and an azulene‐based bisamide unit. Analysis of the crystal structures of the macrocyclic receptors revealed their preference for adopting similar well‐preorganized bent‐sheet conformations, both as free receptors and in their complexes with anions. Studies of the optical properties of both receptors revealed abilities to selectively sense phosphate anions (H2 PO4 −, HP2 O7 3− ), allowing for naked‐eye detection of the presence of these guests in DMSO. Binding studies in solution confirmed that the receptors bind strongly to a series of anions even in highly demanding media, such as mixtures of DMSO with water or with methanol. Comparison of the anion affinity of linear analogues with that of the macrocyclic receptors evidenced the importance of macrocyclic topology. Quantitative analysis revealed that the macrocyclic receptors are selective for H2 PO4 − over other anions. The affinity to H2 PO4 − seen for the symmetrical receptor, containing two azulene‐based subunits, is much higher than for the hybrid macrocycle containing both the azulene‐based and pyridine‐derived subunits. This highlights that the azulene‐based building block serves efficiently as both a binding site and a structure‐preorganizing motif. Abstract : To sense, or not to sense : Azulene‐based macrocyclic receptors that selectively bind HP2 O7 3− and HPO4 − in highly polar media, and change the color of their solutions in the presence of these anions (see figure), while being insensitive to the presence of other anions, have been prepared. X‐ray and NMR structural studies demonstrated excellent preorganization of these molecules for anion binding and revealed their binding modes.